The Role of Service Quality, Customer Satisfaction, Islamic Bank Image, and Financial Information in Enhancing Customer Loyalty - Shoalihin Shoalihin; Asmawati Asmawati; Samsudin Samsudin (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2024)
This study examines the critical role of service quality, customer satisfaction, the image of Islamic banks, and financial information in fostering customer loyalty at KCP BTPN Syariah Kota Bima. Employing a quantitative research method, this investigation utilizes a purposive sampling technique to select 89 customers as respondents. The data collected from these customers are analyzed using multiple linear regression with SPSS version 21 to uncover the relationships and impacts of the studied variables. The findings reveal that service quality significantly contributes to customer loyalty, indicating that superior service delivery fosters stronger customer retention. Additionally, customer satisfaction emerges as a pivotal factor, with satisfied customers demonstrating higher loyalty levels due to their positive experiences and trust in the bank's services. The study further highlights the image of Islamic banks as an influential determinant, suggesting that a favorable reputation and alignment with Islamic values enhance customer commitment. Moreover, financial information proves essential, as transparency and accessibility of financial details build confidence and long-term engagement among customers. The analysis confirms that these factors collectively and individually play a significant role in boosting customer loyalty. These findings underscore the importance of maintaining high service standards, ensuring customer satisfaction, upholding a strong bank image, and delivering clear financial information to sustain customer relationships and loyalty. Ultimately, this research provides valuable insights for Islamic banks aiming to strengthen their customer base and competitive advantage in the financial sector.